Effects of different student response modes on science learning. Issue 8 (17th November 2017) - Kho, Lee Sze; Chen, Chwen Jen
ABSTRACT: Student response systems (SRSs) are wireless answering devices that enable students to provide simple real-time feedback to instructors. This study aims to evaluate the effects of different SRS interaction modes on elementary school students' science learning. Three interaction modes which include SRS Individual, SRS Collaborative, and Classroom were examined. A pretest–posttest quasi-experimental design was used to compare the effects of the three interaction modes on science posttest scores for higher order thinking (HOT) questions as well as lower order thinking questions. The results show that SRS Collaborative mode has significant positive effects on science posttest scores of HOT questions. This study points to the potential benefits of using SRS, particularly for collaborative tasks, to solve problems that require HOT skills.